1998
DOI: 10.3168/jds.s0022-0302(98)75788-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controlled Heat Stress on Ovarian Function of Dairy Cattle. 1. Lactating Cows

Abstract: The objective of this experiment was to determine the effects of controlled heat stress on ovarian function of lactating dairy cows. Estrus was synchronized (estrus = d 0), and cows were randomly assigned to either heat stress (n = 11; 29 degrees C, 60% relative humidity) or thermoneutral (n = 11; 19 degrees C, 60% relative humidity) treatment. For cows undergoing heat stress, ambient temperature (19 degrees C) was increased from d 11 to 13 of the estrous cycle (3.3 degrees C/d increase) and remained at 29 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
111
1
15

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(145 citation statements)
references
References 27 publications
11
111
1
15
Order By: Relevance
“…Although it has been demonstrated that suckling, BCS and heat stress affect ovarian activity, the results obtained in the present trial were acceptable, despite the fact that the cows were suckling their calves, had a low BCS and experienced heat stress due to high ambient temperatures. Although heat stress diminishes particularly the number of small follicles (Wolfenson et al, 1995) and delays luteolysis in cows (Wilson et al, 1998), this was not observed in the present study; on the contrary, PGF 2α induced luteolysis in all cows that had a CL, and the follicles that consequently developed were small (3 to 5 mm) but great in number.…”
Section: Discussioncontrasting
confidence: 44%
“…Although it has been demonstrated that suckling, BCS and heat stress affect ovarian activity, the results obtained in the present trial were acceptable, despite the fact that the cows were suckling their calves, had a low BCS and experienced heat stress due to high ambient temperatures. Although heat stress diminishes particularly the number of small follicles (Wolfenson et al, 1995) and delays luteolysis in cows (Wilson et al, 1998), this was not observed in the present study; on the contrary, PGF 2α induced luteolysis in all cows that had a CL, and the follicles that consequently developed were small (3 to 5 mm) but great in number.…”
Section: Discussioncontrasting
confidence: 44%
“…Ronchi et al (2001) found P4 concentration to be lower in heat-stressed cows, while others have observed higher concentrations of P4 (Wilson et al, 1998). In contrast, Wolfenson et al (1995) found no differences in P4 concentrations between heat-stressed and cooled cows.…”
mentioning
confidence: 78%
“…Por ejemplo, Wilson et al, (1998b) La dinámica folicular es afectada por el estrés calórico, el efecto de dominancia decrece, hay una emergencia temprana del folículo preovulatorio y carencia en la regresión de los folículos subordinados (Wolfenson et al, 1995).El efecto del estrés calórico sobre la dominancia en el desarrollo de ondas foliculares fue también confirmado por Trout et al, (1998). En un experimento in vitro, donde se cultivaron fragmentos ováricos durante 7 días, el complejo cúmulus-ovocito (COC) y ovocitos aislados fueron sometidos a estrés calórico durante las primeras 12 horas del experimento.…”
Section: Respuesta De La Fisiología Reproductivaunclassified
“…Se estima que los efectos del estrés calórico sobre la dinámica ovárica tienen consecuencias en el corto y largo plazo y que para que la dinámica ovárica se normalice deben pasar de 2 a 3 ciclos estrales desde la última afectación por calor (Roth, 2015). Wilson et al (1998b) encontraron que la vida del cuerpo lúteo en vacas cíclicas en condiciones de estrés calórico es más larga y que las concentraciones de progesterona se mantienen significativamente más altas del día 17 al 21 del ciclo estral. El comportamiento del cuerpo lúteo de vida larga observado en vacas bajo estrés calórico, fue el mismo obtenido cuando la evaluación se realizó con novillas, la única diferencia es que las concentraciones altas de progesterona fueron de los días 16 al 20 del ciclo estral.…”
Section: Respuesta De La Fisiología Reproductivaunclassified